2001
DOI: 10.1042/bj3560011
|View full text |Cite
|
Sign up to set email alerts
|

Arg-Tyr-Asp (RYD) and Arg-Cys-Asp (RCD) motifs in dendroaspin promote selective inhibition of β1 and β3 integrins

Abstract: Arg-Gly-Asp (RGD) is a unique minimal integrin-binding sequence that is found within several glycoprotein ligands. This sequence has also been found in snake-venom anti-platelet proteins, including the disintegrins and dendroaspin, a natural variant of short-chain neurotoxins isolated from the venom of Dendroaspis jamesonii. In the present study, the motifs RYD and RCD were introduced into the dendroaspin scaffold to replace RGD. Both motifs in dendroaspin caused inhibition of ADP-induced platelet aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Indeed, the NMR structural studies of several inhibitors including wild-type dendroaspin (34,36) have demonstrated that the positioning of the RGD motif at the apex of a solvent exposed loop is a prerequisite for inhibitory activity. On the other hand, the most potent tripeptide motifs are not limited to only RGD and KGD as our previous studies of RYD and RCD motifs have demonstrated (37).…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, the NMR structural studies of several inhibitors including wild-type dendroaspin (34,36) have demonstrated that the positioning of the RGD motif at the apex of a solvent exposed loop is a prerequisite for inhibitory activity. On the other hand, the most potent tripeptide motifs are not limited to only RGD and KGD as our previous studies of RYD and RCD motifs have demonstrated (37).…”
Section: Discussionmentioning
confidence: 83%
“…10 However, despite the ability of aggretin to induce phosphorylation of endothelial-cell ERK 1/2, confirming its ability to activate ␣2␤1-dependent signaling 26 (Figure 2), aggretin did not inhibit HKa-induced endothelial-cell apoptosis. Identical results were obtained using mAb JBS2, a specific ␣2␤1-activating monoclonal antibody, 44,45 and mAb TS2/16, a specific ␤1 integrinactivating antibody, either in solution or as a coating for microplates on which cells were cultured (not shown). Although these results do not exclude a role for integrin ␣2␤1 in mediating collagen-dependent endothelial-cell survival, they suggest that if such an interaction is important, a more complex ligand-receptor interaction is involved than the monovalent or bivalent interactions associated with aggretin or monoclonal antibodies, respectively.…”
Section: Hka-induced Ros Generation Is Necessary For Apoptosis and Ismentioning
confidence: 84%
“…[17][18][19]45,69 While our results are consistent with such a mechanism, we were not able to demonstrate protection from apoptosis by soluble collagen or by smaller ligands such as aggretin or monoclonal antibodies that activate ␣2␤1. 26,27,44 Thus, we hypothesize that the ability of immobilized collagen to prevent HKa-induced apoptosis may reflect a need for receptor aggregation, or at least engagement by a multivalent ligand, perhaps accompanied by activation of mechanochemical signaling responses not induced by smaller, soluble ligands. 46,47,70 A second hypothesis, that the ability of collagen to quench ROSs may Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…24 They were consistent with the results of different integrin function-blocking mAbs. 25,26 In addition, the adhesion of K562 cells to fibronectin (FN) in the presence of 500 lM Mn 2þ was shown to be predominantly a5b1-dependent. 27 Their inhibitory constants are summarized in Table I.…”
Section: Inhibition Of Cell Adhesion To Fibrinogen and Fibronectinmentioning
confidence: 99%